ASRHR in Ethiopia: reviewing progress over the last 20 years and looking ahead to the next 10 years - Elsie Akwara; Kereta Worknesh; Lemessa Oljiira; Lulit Mengesha; Mengistu Asnake; Emiamrew Sisay; Dagem Demerew; Marina Plesons; Wegen Shirka; Azmach Hadush; Venkatraman Chandra-Moulli (BMC, 2022)
Abstract Over the last two decades, improvements in Ethiopia's socio-economic context, the prioritization of health and development in the national agenda, and ambitious national health and development policies and programmes have contributed to improvements in the living standards and well-being of the population as a whole including adolescents. Improvements have occurred in a number of health outcomes, for example reduction in levels of harmful practices i.e., in child marriage and female genital mutilation/cutting (FGM/C), reduction in adolescent childbearing, increase in positive health behaviours, for example adolescent contraceptive use, and maternal health care service use. However, this progress has been uneven. As we look to the next 10 years, Ethiopia must build on the progress made, and move ahead understanding and overcoming challenges and making full use of opportunities by (i) recommitting to strong political support for ASRHR policies and programmes and to sustaining this support in the next stage of policy and strategy development (ii) strengthening investment in and financing of interventions to meet the SRH needs of adolescents (iii) ensuring laws and policies are appropriately communicated, applied and monitored (iv) ensuring strategies are evidence-based and extend the availability of age-disaggregated data on SRHR, and that implementation of these strategies is managed well (v) enabling meaningful youth engagement by institutionalizing adolescent participation as an essential element of all programmes intended to benefit adolescents, and (vi) consolidating gains in the area of SRH while strategically broadening other areas without diluting the ASRHR focus.